2021
DOI: 10.4103/sjoralsci.sjoralsci_27_21
|View full text |Cite
|
Sign up to set email alerts
|

Nano hydroxyapatite toothpaste as a treatment for dentine hypersensitivity

Abstract: Introduction: Dentin hypersensitivity (DH) is a common and painful clinical occurrence that can negatively impact patients' quality of life. An arsenal of different desensitizing molecules is available on the market, but no gold standard has yet to be set. Aim: The aim of this study was to perform a review on the potential of nano-hydroxyapatite (n-HA) as a desensitizing toothpaste agent as opposed to placebo or other desensitizing molecules. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…F has been considered the most effective caries-inhibiting agent for several decades; however, due to some side effect issues in children and lower public acceptance, another effective alternative is required [ 35 ]. Therefore, some researchers introduced HAP in toothpaste as a substitute for The F. In addition, HAP also acts as a source of calcium and phosphate ions, has a whitening effect, and reduces dental hypersensitization [ 36 , 37 ].…”
Section: Nanomaterialsmentioning
confidence: 99%
“…F has been considered the most effective caries-inhibiting agent for several decades; however, due to some side effect issues in children and lower public acceptance, another effective alternative is required [ 35 ]. Therefore, some researchers introduced HAP in toothpaste as a substitute for The F. In addition, HAP also acts as a source of calcium and phosphate ions, has a whitening effect, and reduces dental hypersensitization [ 36 , 37 ].…”
Section: Nanomaterialsmentioning
confidence: 99%
“…In a comparative study showed that 2.5% Arginine and nHA are equally effective for the management of post-bleaching dentin sensitivity ( Moharam et al, 2022 ). Studies report that there is enhanced clinical performance and dentine hypersensitivity relief using nHA containing agents ( de Melo Alencar et al, 2019 , Oubenyahya, 2021 ). Clinically toothpaste containing either 10% or 15% nHA (10 or 15%) solely or supplemented with potassium nitrate was as effective as calcium sodium phosphosilicate for relief of dentine hypersensitivity symptoms when applied at least twice daily.…”
Section: Applications Of Nanohydroxyapatite In Dentistrymentioning
confidence: 99%
“…There are several agents that have been investigated in the past to conservatively treat DH [ 7 , 8 ]. There have been 8 systematic reviews of therapeutic treatment of dentin hypersensitivity published in the recent past that included studies on hydroxyapatite (HAP) as an active desensitization agent [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ] ( Supplementary Materials : Table S1 ). They included studies on HAP that ranged in number from just one to as many as 20 studies.…”
Section: Introductionmentioning
confidence: 99%